1999
DOI: 10.1021/jp984124y
|View full text |Cite
|
Sign up to set email alerts
|

Excited State Dynamics of a Julolidino Analogue of Crystal Violet:  A Relaxation Path through a Conical Intersection?

Abstract: Transient absorption spectroscopy with subpicosecond time resolution was applied to the study of the excited-state dynamics of an analogue of crystal violet with julolidino-substituted phenyl rings in ethanol, propanol, and butanol at room temperature. Experiments were also carried out with crystal violet for comparison. The time-resolved spectra are interpreted by a barrierless adiabatic photoreaction, leading to the formation of a dark transient excited state involving the torsion of one of the substituted p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(56 citation statements)
references
References 44 publications
4
52
0
Order By: Relevance
“…This has been extensively investigated for photoexcited di-and triphenylmethane dye molecules showing twisting dynamics of the phenyl groups. [212][213][214][215][216] Another example is the diphenyl-aminomethane dye cation auramine ( Figure 18). Auramine is a yellow dye that is weakly fluorescent in low-viscosity solvents (e.g., water) and highly fluorescent in viscous solvents, DNA, and polymeric acids.…”
Section: Auraminementioning
confidence: 99%
“…This has been extensively investigated for photoexcited di-and triphenylmethane dye molecules showing twisting dynamics of the phenyl groups. [212][213][214][215][216] Another example is the diphenyl-aminomethane dye cation auramine ( Figure 18). Auramine is a yellow dye that is weakly fluorescent in low-viscosity solvents (e.g., water) and highly fluorescent in viscous solvents, DNA, and polymeric acids.…”
Section: Auraminementioning
confidence: 99%
“…For example, in several triphenyl dyes with amine substitution, it is reported that the twisting of the anilino group in their excited state is responsible for their low emission yield. [30,31] For para-(N,N-dialkylamino)benzylideneA C H T U N G T R E N N U N G mal-A C H T U N G T R E N N U N G ononitriles, however, based on experimental evidence as well as from theoretical calculations, it was shown that the twisting of the amino group as well as of the anilino group contribute significantly towards the nonradiative decay channel of this molecule in its excited states. [32] Very recently, Saha et al [33] have shown that in dimethyl-aminostyrylbenzothiazole, having a close structural relation with ThT, only the twisting of the amino group is responsible for the fast nonradiative decay in its excited state.…”
Section: Introductionmentioning
confidence: 99%
“…The phenom-enon has been observed for example for photoexcited di-and triphenylmethane dye molecules. Examples are malachite green, 15,[38][39][40] crystal violet 12,13,16,17,24,[26][27][28][33][34][35] and its julolidine analogue, 23,28 ethyl violet, 14,38 and parafuchsin. 14,38 To simulate the temporal behavior of e (t) in such excited state systems, Bagchi, Fleming, and Oxtoby 7 ͑BFO͒ considered the incorporation of a reaction-coordinate dependent ͑nonlocal͒ sink function in the Smoluchowski diffusion equation.…”
Section: Introductionmentioning
confidence: 99%